Perspectives and Practice of HIV Disclosure to Children and Adolescents by Health-Care Providers and Caregivers in sub-Saharan Africa: A Systematic Review - Aderomilehin, Oluyemisi; Hanciles-Amu, Angella; Ozoya, Oluwatobi Ohiole (Frontiers in Public Health, 2016)
Background: Sub-Saharan Africa has the highest prevalence of HIV globally, and this is due to persistent new HIV infections and decline in HIV/AIDS-related mortality from improved access to antiretroviral therapy. There is a limited body of work on perspectives of healthcare providers concerning disclosing outcomes of HIV investigations to children and adolescents in Sub-Saharan Africa. Most studies are country-specific, indicating a need for a regional scope. Objective: To review the current literature on the perspectives of healthcare providers and caregivers of children and adolescents on age group-specific and culture-sensitive HIV disclosure practice. Methods: Electronic database search in PubMed, Google scholar and the University of South Florida (USF) Library Discovery Tool (January 2006 up to February 2016). Further internet search was conducted using the Journal Author Name Estimator (JANE) search engine and extracting bibliographies of relevant articles. Search terms included ‘disclosure*’, ‘HIV guidelines’, ‘Sub-Saharan Africa’, ‘clinical staff’, ‘ART’, ‘antiretroviral adherence’, ‘People living with HIV’, ‘pediatric HIV’, ‘HIV’, ‘AIDS’, ‘healthcare provider’ (HCP), ‘caregiver’, ‘adolescent’, ‘primary care physicians’, ‘nurses’, ‘patients’. Only studies related to HIV/AIDS disclosure, healthcare providers, caregivers that clearly described perspectives and interactions during disclosure of HIV/AIDS sero-status to affected children and adolescents were included. Independent extraction of articles was conducted by reviewers using predefined criteria. Nineteen articles met inclusion criteria. Most studies were convenience samples consisting of combinations of children, adolescents, HCPs and caregivers. Key findings were categorized into disclosure types, prevalence, facilitators, timing, process, persons best to disclose, disclosure setting, barriers and outcomes of disclosure. Conclusions: Partial disclosure is appropriate for children in SSA up to early adolescence. Caregivers should be directly involved in disclosing to children but they require adequate disclosure support from HCPs. Full disclosure is suitable for adolescents. Adolescents prefer disclosure by HCPs and they favor peer-group support from committed peers and trained facilitators, to reduce stigma. Healthcare providers need continuous training and adequate resources to disclose in a patient-centered manner.